Vehicle platooning scheme based on two-way auction - LIU Hai; WU Jinyu; WANG Tianxi; PENG Hongye (Tongxin xuebao)
Vehicles positioned at varying locations in the platoon exhibit differing levels of energy consumption, which may result in the platoon breaking up during travel or even prevent successful formation of the platoon. To solve this problem, a vehicle platooning scheme based on two-way auction was proposed. Specifically, the positions in the vehicle platooning were considered as a special commodity to be auctioned. By requesting a price from the platoon leader and a bid from the platoon follower, the position of each vehicle participating in the platooning was determined. Furthermore, an incentive compatible platooning compensation mechanism was devised that could motivate the vehicles in the platoon to maintain their position while traveling. Theoretical analysis and extensive experiments show that, the proposed scheme can not only realize the vehicle platooning efficiently, but also ensure the stability of the formed platoon.